Future directions for green chemistry in Indian pharmaceuticals: a survey-based analysis - K, VENKATESWARA RAJU; PRIYANKA, BADUGU; NORI, LAKSHMI PRASANTHI (Prospects in Pharmaceutical Sciences, 2025)
Green chemistry, focused on the sustainable design and production of chemicals, aligns with global efforts to mitigate environmental harm and promote resource efficiency. Regulatory considerations are crucial in advancing green chemistry practices and minimizing environmental impact. Key regulatory frameworks such as the Toxic Substances Control Act (TSCA) in the United States and the Registration, Evaluation, Authorisation, and Restriction of Chemicals Act (REACH) in Europe mandate assessment and management of chemical risks. These regulations drive innovation by encouraging the substitution of hazardous substances with safer alternatives and promoting sustainable processes. Compliance with regulatory standards not only ensures environmental protection, but also fosters industry competitiveness and supports public health goals. This research article underscores the implementation of green chemistry in Indian pharmaceutical companies through a survey conducted through a questionnaire filled by employees of various pharma industries across India on issues related environmental/sustainability goals and targets, use of green chemistry, barriers to greater adoption of GC by Indian pharmaceutical companies, external GC collaborations, use of GC resources by Indian pharmaceutical companies, use of green chemistry metrics by Indian pharmaceutical companies, and the reported stage in the waste management hierarchy. From the analysis we found it satisfactory, and also that this requires further in-depth investigation.